Virtual Cocrystal Screening of Adefovir Dipivoxyl: Identification of New Solid Forms with Improved Dissolution and Permeation Profiles - Rafael Barbas; Hanan Fael; Samuel Lee; Rebeca Ruiz; Christopher A. Hunter; Elisabet Fuguet; Clara Ràfols; Rafel Prohens (MDPI AG, 2022)
The application of a computational screening methodology based on the calculation of intermolecular interaction energies has guided the discovery of new multicomponent solid forms of the oral antiviral Adefovir Dipivoxyl. Three new cocrystals with resorcinol, orcinol and hydroquinone have been synthesized and thoroughly characterized. They show improved dissolution profiles with respect to the single solid form, particularly the cocrystals of orcinol and resorcinol, which have 3.2- and 2-fold faster dissolution rates at stomach conditions (pH 1.5). Moreover, dynamic dissolution experiments that simultaneously mimic both the pH variation along the gastrointestinal tract and the partition into biological membranes show that, in addition to the faster initial dissolution, Adefovir Dipivoxyl also penetrates faster into the organic membranes in the form of resorcinol and orcinol cocrystals.